The privacy paradox – Investigating discrepancies between expressed privacy concerns and actual online behavior – A systematic literature review - Barth, Susanne; de Jong, Menno D.T. (Telematics and informatics, 2017)
•This paper presents a systematic literature review discussing the privacy paradox.•Users are concerned about their privacy but undertake little to protect their data.•Risk-benefit evaluation or little risk assessment drives information disclosure.•Design solutions of mobile apps should be adapted to different cognitive styles.•Support users through automated user-centered systems and user-friendly interface. Also known as the privacy paradox, recent research on online behavior has revealed discrepancies between user attitude and their actual behavior. More specifically: While users claim to be very concerned about their privacy, they nevertheless undertake very little to protect their personal data. This systematic literature review explores the different theories on the phenomenon known as the privacy paradox. Drawing on a sample of 32 full papers that explore 35 theories in total, we determined that a user’s decision-making process as it pertains to the willingness to divulge privacy information is generally driven by two considerations: (1) risk-benefit evaluation and (2) risk assessment deemed be none or negligible. By classifying in accordance with these two considerations, we have compiled a comprehensive model using all the variables mentioned in the discussed papers. The overall findings of the systematic literature review will investigate the nature of decision-making (rational vs. irrational) and the context in which the privacy paradox takes place, with a special focus on mobile computing. Furthermore, possible solutions and research limitation issues will be discussed.